Climate change and Singapore - Lee, Kay Li. (2011)
The Northern Sea Route (NSR), located in the Arctic, is a shipping route linking the Pacific and Atlantic Ocean. The heightened focus on the Arctic of late is primarily due to the impacts of climate change and the fact that these changes are occurring at an unprecedented rate in this region. Presently, ships can pass the NSR two to three months a year. With the thawing of the Arctic ice, not only will the NSR be passable for longer periods of time, Arctic offshore resources will be more accessible as well. The objectives of this research project aims to investigate the potential impacts on Singapore as a major Hub; and to identify business opportunities for Singapore and the local maritime industries.